Methodological Study of Tafsir Yasin by K.H. Abd. Basith Ulama from Madura - Ulfatun Hasanah; Moh. Ashif Ashif Fuadi; Fitrotul Muzayanah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2023)
This study explains the study of Tafsir Yasin through books by Nusantara scholars. K. H. Abdul Basith AS from Madura is quite productive in producing works, including the book of Tafsir Yasin. Through qualitative methods with a literature study approach, this study resulted in conclusions: first, the interpretation of surah yasin by K.H. Abd. Basith presents the values of the Qur'an in life as a form of interpretation that ma'tsur, tahlili, and adabi-ijtima'i. Second, the 83 verses are divided into 14 parts with explanations of verses and advice on social reality. This reason is due to the initial purpose of writing the tafsir, which was to provide an understanding to the unfamiliar public of the meaning contained in the reading of surah yasin. Third, it is also to make people aware that the recitation of surah yasin is not solely because of customs and traditions, such as the yasinan tradition by the majority of the nahdliyin, but because of the many privileges and virtues contained in it.